'New' humanitarianisms and programming: the encounter of Turkey and Europe with Syrian refugees. Issue 3 (4th May 2019) - Cetinoglu, Talita
ABSTRACT: This article highlights the intervention strategies of Turkey and Europe in response to the Syrian refugee movement. Focusing on Turkey's state-led humanitarianism, it highlights the affinity to 'Western' humanitarianism with regard to humanitarianism as an instrument of interventionism. It shows how these different approaches contributed to a weak protection framework, and how they translated into humanitarian programming that accommodates both parties. This contribution thus concludes that the distinction between 'Western' and 'non-Western' humanitarianisms must be unpacked by analysing how various actors make use of and reproduce this construct to position and negotiate the terms of humanitarian actions, and not be analysed or understood as essentialist categories that explain action.